The role of accounting information quality measures in making administrative decisions in the light of situational theory - Sroor Najim Abdullah; Maher Ali Hussein alshamam (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The quality of accounting information is considered a vital factor in the modern information era, as it significantly impacts the decision-making processes within economic institutions. This study aims to comprehend the influence of accounting information quality on the decision-making process through the dimensions of accounting information quality (accuracy, relevance, effectiveness, predictability, efficiency) within the framework of the standpoint theory. The standpoint theory provides a theoretical framework that focuses on how social, cultural, political, and institutional factors affect managerial decision-making processes, as well as how individuals form standpoints, values, and standpoint beliefs. Based on the analysis of hypotheses and conclusions drawn from the results, the study found a strong positive and statistically significant relationship between the quality of accounting information and decision-making within the standpoint theory framework. The results indicated that an increase in accounting information quality corresponds to an enhancement in the ability to make well-informed and deliberate decisions, thereby boosting confidence in result accuracy. This study serves as an important reference for researchers and decision-makers in the fields of accounting and management. It underscores the significance of accounting information quality in sustaining and succeeding within the dynamic business market. The standpoint theory highlights its role in comprehending the accounting process and enhancing the performance of managerial decisions.